ENTREPRENEURS' POLITICAL COMMUNICATION STRATEGIES IN REGIONAL HEAD ELECTIONS - Pratiwi, Endah (TOPLAMA, 2024)
The aim of this research was to determine the role of political branding and personal branding in the choice of regional heads. This research used a qualitative approach. This type of research was qualitative descriptive research. Data collection methods using interviews, documentation techniques. The research results showed that political branding during the regional election campaign is formed through self-identification, namely character, abilities, values, political products, ideas, positioning, namely constituent segmentation, personality, key political messages, interpretation. Personal branding in supporting his candidacy to become deputy mayor is explained by appearance, leadership style, visibility and personality. The reason for entrepreneurs' strategies with political branding and personal branding during the campaign period is because branding strategies provide symbolic value in terms of identification, meaning, value, benefits, promises and differentiation of a political product. Political branding and personal branding are considered capable of influencing perceptions and providing confidence to constituents. Political branding and personal branding are the results of interactions and emotional attachments that exist between political contestants and their constituents.